Unlocked - Kingsbury, Karen (Grand Rapids, Mich. : Zondervan, 2010)
Holden Harris is an autistic eighteen-year-old who is bullied at school. Ella Reynolds is the head cheerleader who befriends Holden but has problems of her own at home.
Includes discussion questions (p. 321-323).
Keywords: Autistic children -- Fiction; School violence -- Fiction; Bullying -- Fiction; Adultery -- Fiction; Domestic fiction; Christian fiction